ABOUT THE TASHKENT STATE UNIVERSITY OF LAW - Kudratillaev Khazratali Zokirjon ugli (Western European Studies, 2025)
The article provides an overview of Tashkent State University of Law, including the educational institution's history, the organization of its academic programs, and information about the university's existing faculties
Keywords: Узбекистан; юриспруденция; ТГЮУ